2018
DOI: 10.1101/255372
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In vivo optochemical control of cell contractility at single cell resolution by Ca2+ induced myosin activation

Abstract: AbstractsThe spatial and temporal dynamics of cell contractility plays a key role in tissue morphogenesis, wound healing and cancer invasion. Here we report a simple, single cell resolution, optochemical method to induce minute-scale cell contractions in vivo during morphogenesis. We employed the photolabile Ca 2+ chelator o-nitrophenyl EGTA to induce bursts of intracellular free Ca 2+ by laser photolysis. Ca 2+ bursts appear within seconds and are restricted to individual target cells. Cell contraction reliab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This experiment provided the first evidence that calcium is necessary for neural tube closure. Recent studies using vertebrate model organisms including zebrafish, Xenopus , and mice have supported the idea that calcium is a major regulator of neural tube closure [ 4 , 66 , 67 , 68 ]. Visualization of calcium influxes during neural tube closure using genetically encoded calcium indicator showed distinct spikes and waves.…”
Section: Calcium Activity During Development and Its Role In Diseamentioning
confidence: 99%
See 1 more Smart Citation
“…This experiment provided the first evidence that calcium is necessary for neural tube closure. Recent studies using vertebrate model organisms including zebrafish, Xenopus , and mice have supported the idea that calcium is a major regulator of neural tube closure [ 4 , 66 , 67 , 68 ]. Visualization of calcium influxes during neural tube closure using genetically encoded calcium indicator showed distinct spikes and waves.…”
Section: Calcium Activity During Development and Its Role In Diseamentioning
confidence: 99%
“…When this actin activity is imaged using F-actin marker Lifeact-EGFP at the same time as calcium activity, F-actin mesh-like structures develop in the center of the cells following the calcium transients during neural tube closure in Xenopus [ 4 ]. In addition, calcium transients trigger non-muscle myosin II activation within a minute of their occurrence in Xenopus and Drosophila [ 4 , 64 , 67 ].…”
Section: Calcium Activity During Development and Its Role In Diseamentioning
confidence: 99%
“…Optochemical approaches have similarly enabled control of other cytoskeletal elements such as myosins involved in cell contraction. For instance, light-induced bursts of calcium emerging from a photolabile Ca 2+ chelator onitrophenyl EGTA could stimulate cell contraction and consequently tissue morphogenesis via local non-muscle myosin II activation [124].…”
Section: Control the Dynamics Of The Cytoskeletonmentioning
confidence: 99%
“…In germ-band epithelium Ca 2+ uncaging induced, sudden Ca 2+ bursts trigger cell contractions (Kong et al, 2019). These findings suggest that actomyosin cytoskeleton can be actively reorganized in a Calcium-dependent manner to drive contractility (Fig 1 .12, A).…”
Section: Calcium Signaling In Drosophila Developmentmentioning
confidence: 91%
“…During smooth muscle contraction, it is known that myosin II activation is regulated by Ca 2+ /calmodulin complex that activates myosin light chain (MLC) via MLC kinase (Fig 1 .13, B) (Kitazawa et al, 1991). Recent studies in the epithelium, have shown that intracellular Ca 2+ dependent non-muscle myosin II activation could be mediated via Rho kinase activity (Rok) (Kong et al, 2019). Yet the detailed mechanism of how Ca 2+ can regulate actomyosin networks remained elusive so far in the non-muscle cells.…”
Section: Calcium Signaling In Drosophila Developmentmentioning
confidence: 99%